2019
DOI: 10.1111/tmi.13240
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends and differential patterns in the prevalence of severe anaemia in India: observations from country‐wide haemoglobin determinations 2008–2018

Abstract: Objectives To assess temporal trends in the occurrence of severe anaemia in India over the past decade, encompassing every state and union territory. Methods For the period 2008–09 to 2017–18, annual estimates (%) of severe anaemia (haemoglobin < 7 g/dl) for India were derived from Health Management Information System datasets, along with 95% confidence intervals (CIs) to construct temporal trends. Differential patterns in the distribution of severe anaemia by geography, epidemiological transition level and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Prior to 1990, Cañizares et al indicated that the prevalence of anemia in Ecuador differed markedly according to the areas of the country, which partially agrees with our study [39]. Other studies also reported significant variation in anemia prevalence across geographical regions [40]. According to Elzahaf and Omar, the variation in the prevalence of anemia across regions, provinces and cities may be due to characteristics and nutritional habits of the population [41].…”
Section: Plos Onesupporting
confidence: 90%
“…Prior to 1990, Cañizares et al indicated that the prevalence of anemia in Ecuador differed markedly according to the areas of the country, which partially agrees with our study [39]. Other studies also reported significant variation in anemia prevalence across geographical regions [40]. According to Elzahaf and Omar, the variation in the prevalence of anemia across regions, provinces and cities may be due to characteristics and nutritional habits of the population [41].…”
Section: Plos Onesupporting
confidence: 90%
“…The HMIS is a Government of India initiative that helps in monitoring NHM and other health programmes. It may be harnessed for programme evaluation, gap analysis, epidemiological insights, and health systems research (28)(29)(30)(31)(32). The HMIS network compiles monthly information regarding various health indicators (such as patient services, ANC, family planning, immunization, etc.)…”
Section: Data Sourcementioning
confidence: 99%
“…3 Additionally, severe anemia, defined as hemoglobin (Hb) levels <7 g/dL, continues to be a substantial problem despite Indian guidelines and a focus on eradicating anemia. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%